Diamond Concept as Principle for the Development of Spinal Cord Scaffold: A Literature Review - Sakti, Yudha M.; Malueka, Rusdy Ghazali; Dwianingsih, Ery Kus; Kusumaatmaja, Ahmad; Mafaza, Akbar; Emiri, Deas Makalingga (Open Access Macedonian Journal of Medical Sciences, 2021)
INTRODUCTION: Spinal cord injury (SCI) has been bringing detrimental impacts on the affected individuals. However, not only that, it also brings a tremendous effect on the socioeconomic and health-care system. Treatment regimen and strategy for SCI patient have been under further research. DISCUSSION: The main obstacles of regeneration on neuronal structure are the neuroinflammatory process and poor debris clearance, causing a longer healing process and an extensive inflammation process due to this particular inflammatory process. To resolve all of the mentioned significant issues in SCIs neuronal regeneration, a comprehensive model is necessary to analyze each step of progressive condition in SCI. In this review, we would like to redefine a comprehensive concept of the “Diamond Concept” from previously used in fracture management to SCI management, which consists of cellular platform, cellular inductivity, cellular conductivity, and material integrity. The scaffolding treatment strategy for SCI has been widely proposed due to its flexibility. It enables the physician to combine another treatment method such as neuroprotective or neuroregenerative or both in one intervention. CONCLUSION: Diamond concept perspective in the implementation of scaffolding could be advantageous to increase the outcome of SCI treatment.